The effects of physical exercise on college students’ pro-social behavior: the chain mediating role of sense of meaning in life and subjective well-being - Jiang, Yong; Bian, Tianqi (Frontiers in Psychology, 2025)
To explore the relationship between the sense of meaning of life and subjective well-being in college students’ physical exercise and pro-social behavior. A scale was used to measure 626 college students, and SPSS27.0 and Process4.1 were used for statistical analysis. Results (1) college students’ physical exercise, sense of meaning in life, subjective well-being and pro-social behavior were positively correlated. (2) Physical exercise significantly and positively predicted college students’ pro-social behavior (β = 0.284, p < 0.001); the effect value of the indirect effect path 1 was 0.0028 (physical exercise → sense of meaning in life → pro-social behavior), which accounted for 31.11% of the total effect; the effect value of the indirect effect path 2 was 0.0007 (physical exercise → sense of meaning in life → pro-social behavior). The effect value of indirect effect path 1 is 0.0028 (physical exercise → sense of meaning in life → subjective well-being → pro-social behavior) which accounts for 31.11% of the total effect; the effect value of indirect effect path 2 is 0.0007 (physical exercise → subjective well-being → pro-social behavior) which accounts for 7.78% of the total effect; and the effect value of indirect effect path 3 is 0.0013 (physical exercise → sense of meaning in life → subjective well-being → pro-social behavior) which accounts for 14.44% of the total effect. Therefore, physical exercise has a direct effect on the pro-social behavior of college students, and can also indirectly affect pro-social behavior through the sense of meaning of life and subjective well-being.